Entrepreneurship and successful firms around world - Šimonová, Berta (2020)
Entrepreneurship nowadays is recognized as a critical resource in the economic development process of a country. Given this fact entrepreneurship development received serious attention among the policymakers, planners, and economists as a strategy of economic growth. The literature review is focusing on the introduction of the importance of entrepreneurial activity, emphasizing the importance of innovation closely related to reflecting on the current and future trends in entrepreneurship. In further chapters of the theoretical part of the thesis, the steps necessary to encounter are described to achieve success and maintain the sustainable development of the business. The empirical part of the work is processing secondary data that is going to show what were the key factors that helped Google and Microsoft become successful and how these two companies were growing. At the end of this part there is going to be a comparison of search engines from Google and Microsoft. Various similarities and differences will be shown to see why Google’s search engine is more popular than Microsoft’s search engine, called Bing.